Gender-specific aspects related to type of fertility preservation strategies and access to fertility care. (27th October 2020) - Perachino, Marta; Massarotti, Claudia; Razeti, Maria Grazia; Parisi, Francesca; Arecco, Luca; Damassi, Alessandra; Fregatti, Piero; Solinas, Cinzia; Lambertini, Matteo
Abstract : Survivorship is an area of paramount importance to be addressed as early as possible after cancer diagnosis by all health care providers. On this regard, cancer care in young patients often poses several age-related considerations among which fertility and pregnancy-related issues have a crucial role. According to the available guidelines on the topic, all patients with cancer diagnosed during their reproductive years should be provided a proper oncofertility counselling before starting anticancer treatments. This is an important step in order to inform patients about the potential treatment-induced gonadotoxicity and the available strategies for fertility preservation so that they can be referred as early as possible to fertility specialists if potentially interested in these options. In this manuscript, we aim to provide an up to date overview on the available efficacy and safety data with the main strategies for fertility preservation in male and female cancer patients in order to help optimising the oncofertility counselling performed by healthcare providers involved in cancer care and dealing with young patients. In male patients with cancer, sperm cryopreservation is the standard technique for fertility preservation. Oocyte/embryo cryopreservation, ovarian tissue cryopreservation and temporary ovarian suppression with luteinising hormone-releasing hormone agonists during chemotherapy are the main options in female patients with cancer. A multidisciplinary management building a strong network between fertility and oncology/haematology units is crucial to properly address fertility care in all young patients with cancer, at both diagnosis and during oncologic follow-up. Discussing fertility and pregnancy-related issues with young patients with cancer has to be considered mandatory nowadays keeping in mind that returning to a normal life (including the possibility to have a family and to live with as few side effects as possible) should be considered an important ambition in cancer care in the 21st century .